A Systematic Review and Meta-Analysis of Phytoestrogen Protects Against Myocardial Ischemia/Reperfusion Injury: Pre-Clinical Evidence From Small Animal Studies - Wang, Yumeng; Shou, Xintian; Fan, Zongjing; Cui, Jie; Xue, Donghua; Wu, Yang (Frontiers in Pharmacology, 2022)
Background: Phytoestrogens (PE) are a class of natural compounds that are structurally similar to estrogens. They have been identified to confer potent cardioprotective effects in experimental myocardial ischemia-reperfusion injury (MIRI) animal models. We aimed to investigate the effect of PE on MIRI and its intrinsic mechanisms. Methods: A systematic search was conducted to identify PEs that have been validated in animal studies or clinical studies as effective against MIRI. Then, we collected studies that met inclusion and exclusion criteria from January 2016 to September 2021.The SYRCLE's RoB tool (32) was used to evaluate the quality. Data were analyzed by STATA 16.0 software. Results: The search yielded 18 phytoestrogens effective against heart disease. They are genistein, quercetin, biochanin A, formononetin, daidzein, kaempferol, icariin, puerarin, rutin, notoginsenoside R1, tanshinone IIA, ginsenoside Rb1, ginsenoside Rb3, ginsenoside Rg1, ginsenoside Re, resveratrol, polydatin, and bakuchiol. Then, a total of 20 studies from 17 articles with a total of 355 animals were included in this meta-analysis. The results show that PE significantly reduced the myocardial infarct size in MIRI animals compared with the control group (p <0.001).PE treatment significantly reduced the creatine kinase level (p < 0.001) and cTnI level (p < 0.001), increased left ventricular ejection fraction (p < 0.001) and left ventricular fractional shortening (p < 0.001) in MIRI animals. In addition, PE also exerts a significant heart rate lowering effect (p < 0.001). Conclusion: Preclinical evidence suggests that PE can be multi-targeted for cardioprotective effects in MIRI. More large animal studies and clinical research are still needed in the future to further confirm its role in MIRI.